2013
DOI: 10.1007/s00701-013-1794-x
|View full text |Cite
|
Sign up to set email alerts
|

Angiographic characteristics of ruptured paraclinoid aneurysms: risk factors for rupture

Abstract: Rupture risk of the paraclinoid aneurysm is very low. However, superiorly located paraclinoid aneurysms appear more likely to rupture than other locations. Angiographically, more conservative indication for the treatment of paraclinoid aneurysm should be recommended except for superior located lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 40 publications
1
8
0
Order By: Relevance
“…However, approximately one-third of patients with their OA occluded/narrowed meanwhile experienced new complications. Considering that paraclinoid aneurysms can grow to a large size and have a lower rate of rupture compared to other aneurysms, the source of new symptoms—either from OA occlusion or mass effect caused by coils or IA thrombogenesis—is difficult to pinpoint 71 . Additionally, no new symptoms were observed in patients with a PICA covered by FDSs.…”
Section: Discussionmentioning
confidence: 99%
“…However, approximately one-third of patients with their OA occluded/narrowed meanwhile experienced new complications. Considering that paraclinoid aneurysms can grow to a large size and have a lower rate of rupture compared to other aneurysms, the source of new symptoms—either from OA occlusion or mass effect caused by coils or IA thrombogenesis—is difficult to pinpoint 71 . Additionally, no new symptoms were observed in patients with a PICA covered by FDSs.…”
Section: Discussionmentioning
confidence: 99%
“…There was no significant correlation between recurrence rates depending on the projection of aneurysm in our study. Oh et al 19) reported that superiorly located paraclinoid aneurysms appear more likely to rupture than other locations in an analysis of 265 paraclinoid aneurysms. Lee et al 12) reported rupture in four out of eight dorsal wall aneurysms which showed rapid growth and configurational change.…”
Section: Discussionmentioning
confidence: 99%
“…7 Several studies identified irregular dome morphology as an independent risk factor of aneurysm rupture when compared with single-sac aneurysm configuration. [8][9][10][11] Although aneurysms with irregular dome shape or multiple sacs account for 30% of UIAs, data on their particular treatment are rare. 12 A widespread classification of aneurysm shape was proposed by the authors of International Study of Unruptured Intracranial Aneurysms (ISUIA) dividing aneurysms into single-sac aneurysms with smooth or irregular margin and aneurysms with daughter sacs as well as multilobe aneurysms.…”
Section: Postoperative Cerebral Ischemiamentioning
confidence: 99%